2006
DOI: 10.1002/hon.776
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular lymphoma: a neoplasm of ‘homeless’ lymphocytes?

Abstract: Intravascular lymphoma (IVL) is an extremely rare form of non-Hodgkin lymphoma characterized by almost exclusive growth of neoplastic lymphocytes within blood vessel lumen. IVL is morphologically characterized in most instances by large cells with B-cell lineage. IVL is an aggressive and usually disseminated disease that predominantly affects elderly patients, resulting in poor PS, B-symptoms, anemia, and high lactate dehydrogenase serum level. The brain and skin are the most commonly involved sites; nodal dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
135
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(144 citation statements)
references
References 78 publications
(125 reference statements)
6
135
1
Order By: Relevance
“…The median age of presentation is 70 with similar prevalence in males and females [6]. It has been reported that about 15% of IVL patients have had a previous or concomitant malignancy with NHL being the most commonly associated hematopoietic malignancy [6].…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…The median age of presentation is 70 with similar prevalence in males and females [6]. It has been reported that about 15% of IVL patients have had a previous or concomitant malignancy with NHL being the most commonly associated hematopoietic malignancy [6].…”
Section: Commentarymentioning
confidence: 99%
“…It has been reported that about 15% of IVL patients have had a previous or concomitant malignancy with NHL being the most commonly associated hematopoietic malignancy [6]. Clinical features are heterogeneous and frequently include B symptoms, fever of unknown origin, and poor performance status [6][7][8][9][10][11].…”
Section: Commentarymentioning
confidence: 99%
“…Besides the unusual association of HLH with IVL in European patients, there are other features that do not favor a classical IVL in this case. In fact, brain pathology resembled primary diffuse large B‐cell lymphoma of the CNS and while some cases of IVL have brain mass‐like lesions 11, IVL with secondary CNS involvement usually have brain vessel and leptomeningeal infiltration 9 not seen in this case. It is thus plausible to assume a primary diffuse large B‐cell lymphoma of the CNS with synchronous IVL.…”
Section: Discussionmentioning
confidence: 77%
“…T‐cell lymphoma and Epstein‐Barr virus infection are the most common causes of adult HLH 1, 2, 3. B‐cell lymphoma presenting with HLH is less common and it is mostly seen in the Asian‐variant of IVL 9, but not in western countries 9, 10. Besides the unusual association of HLH with IVL in European patients, there are other features that do not favor a classical IVL in this case.…”
Section: Discussionmentioning
confidence: 99%
“…That biopsy was characteristic of IVL with multiple cortical vessels (M4 branches) pathologically distended with neoplastic lymphocytes positive for CD20 by immunohistochemistry. Biopsies of the central nervous system in IVL patients have revealed neoplastic lymphocytes within large and medium arteries, distal cortical vessels, leptomeningeal perforators, capillaries, and even veins [2][3][4][5][6] Department of Radiology, University of Utah, Salt Lake City, UT 84132, USA also highly variable. The resolution of current vwMRI protocols, 0.5-0.7 mm voxels, does not allow reliable assessment of the distal intracranial vessels, which introduces the possibility of a false negative study, as in the case of our patient.…”
mentioning
confidence: 99%